2013
DOI: 10.1371/journal.ppat.1003492
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Protective Antigens by Tissue-Stage Nematode Larvae Revealed by Proteomic Analysis and Vaccination-Induced Sterile Immunity

Abstract: Gastrointestinal nematode parasites infect over 1 billion humans, with little evidence for generation of sterilising immunity. These helminths are highly adapted to their mammalian host, following a developmental program through successive niches, while effectively down-modulating host immune responsiveness. Larvae of Heligmosomoides polygyrus, for example, encyst in the intestinal submucosa, before emerging as adult worms into the duodenal lumen. Adults release immunomodulatory excretory-secretory (ES) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 69 publications
5
45
0
Order By: Relevance
“…The abundance of this subfamily of proteins was also confirmed by the 2D gel analysis, where almost 70% of the spots identified presented a single or double CAP motif. We identified more than 30 SCP/TAPS proteins in the ESP of L3 and adult stages from N. brasiliensis, which is in accordance with the diversity of this group of proteins in most nematodes (57), most notably hookworms, where they constitute more than 30% of the adult worm ESP (26,79). Most of the SCP/TAPS proteins from N. brasiliensis were secreted only by adult worms, and only three proteins were detected from L3 ESP, and one protein (m259086) was common to the ESP of both developmental stages.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The abundance of this subfamily of proteins was also confirmed by the 2D gel analysis, where almost 70% of the spots identified presented a single or double CAP motif. We identified more than 30 SCP/TAPS proteins in the ESP of L3 and adult stages from N. brasiliensis, which is in accordance with the diversity of this group of proteins in most nematodes (57), most notably hookworms, where they constitute more than 30% of the adult worm ESP (26,79). Most of the SCP/TAPS proteins from N. brasiliensis were secreted only by adult worms, and only three proteins were detected from L3 ESP, and one protein (m259086) was common to the ESP of both developmental stages.…”
Section: Discussionsupporting
confidence: 82%
“…Superoxide dismutase is an anti-oxidative protein and is involved in protection of N. brasiliensis and Ancylostoma ceylanicum against reactive oxygen species from host inflammatory cells (56). Different apyrases have been described also in the related nematode H. polygyrus (57), and they have been related with clot prevention in blood-feeding arthropods and nematodes (39, 58 -60) and anti-coagulant. The protein acetylcholinesterase has been extensively described in N. brasiliensis and other nematodes and has a role in the inhibition of secretory responses by hydrolyzing acetylcholine (61) and in the reduction of inflammation (62).…”
Section: Discussionmentioning
confidence: 99%
“…The striking role of the activating IgG receptor FcgRI (CD64) in larval immobilization by alternatively activated MF was unexpected due to the well-described involvement of this receptor in type 1 responses such as autoimmunity and protection against bacterial infection (35). Moreover, infection with the intestinal nematode H. polygyrus bakeri is associated with high levels of IgG1 in IS from challenge-infected or vaccinated mice, which has therefore been suggested to be the most relevant Ab isotype for protection (16,42,43). However, IgG1 or IgG1 immune complexes have been reported to bind to FcgRs II and III, but not FcgRI (30,44).…”
Section: Discussionmentioning
confidence: 99%
“…However, IgG1 or IgG1 immune complexes have been reported to bind to FcgRs II and III, but not FcgRI (30,44). Yet, even if sterile immunity after vaccination with excretory secretory products from both tissue and adult stages of H. polygyrus bakeri was associated with high IgG1 titers, no protective IgG1 mAb has been identified to date (42,45). Very recently, it was shown that IgG1 is indeed dispensable for protection against challenge infection with Hpb (46).…”
Section: Discussionmentioning
confidence: 99%
“…Current research is focused on the identification of products or receptors that parallel the connection between TLR and Th1 mediated immunity. Complications are inherent in this process as the products derived from worms may be stage specific with proteins relevant to the egg, larval or adult worm stage, which may colonize different sites in the host; although, there is some indication of an overlap of products among stages of Hb [30]. To date, there is little information on the existence of a common worm/egg derived product that can be linked to the type 2 immune response; however, it is possible that worms that infect a common site, such as the intestine, could induce a common factor.…”
Section: Worm-derived Productsmentioning
confidence: 99%